2005
DOI: 10.1007/s11249-004-3594-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermal atomic oxygen interaction with MoS2 lubricants and relevance to space environmental effects in low earth orbit – effects on friction coefficient and wear-life

Abstract: Wear-life of the MoS 2 film was evaluated by in situ tribological testing under 5 eV atomic oxygen exposures which simulated atomic oxygen environment in low Earth orbit. A combination of a laser-detonation atomic oxygen source and a conventional pinon-disk friction tester was used to perform tribological tests. It was confirmed that the friction coefficient was not affected by atomic oxygen exposure when atomic oxygen fluence was low; however, the friction coefficient increased with increasing atomic oxygen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 9 publications
2
41
0
Order By: Relevance
“…This was confirmed by AES analysis of the wear track (Fig. 5) [17]. Relationship between atomic oxygen flux and wear-life is represented in Fig.…”
Section: Tribological Properties Of Atomic Oxygen-exposed Mossupporting
confidence: 58%
“…This was confirmed by AES analysis of the wear track (Fig. 5) [17]. Relationship between atomic oxygen flux and wear-life is represented in Fig.…”
Section: Tribological Properties Of Atomic Oxygen-exposed Mossupporting
confidence: 58%
“…Formation of molybdenum oxide and carboxyl group at the sample surface caused increase in surface oxygen. The overall changes in surface composition observed in this study basically agree with that reported previously [12].…”
Section: Introductionsupporting
confidence: 92%
“…High-energy particulate radiation is predominantly trapped radiation like EL (up to several MeV) and Pr (up to several hundred MeV). The primary effects of these particulate radiations on materials are ionization, phonon excitations and atomic displacement, resulting in crosslinking, chain scission or polymerization [29]. The major atmospheric constituent in LEO is atomic oxygen (AO) from photo-induced dissociation of O 2 in the upper atmosphere.…”
Section: Diamond-like Carbon Filmsmentioning
confidence: 99%